WTE222 - Computer Aided Design of Wood Product / Faculty of Applied Sciences - UiTM, Faculty of Applied Science (Universiti Teknologi MARA, 2021)
This course provides students with a through introduction into traditional technical drawing and Computer-Aided-Design (CAD) with a focus on wood design. By using popular CAD software in hands-on exercises, students gain the capability to create and distribute industry-standard architectural drawings.